(untitled) (Journal of Governance and Development (JGD), 2015)
The impact of social entrepreneurship on any community can be felt when it touches the lives of the people living in that community. Most of the rural communities especially in Africa suffer from human development amidst untapped resources, this creates an impression of a doomed society, mostly poverty surrounded environment where impacts can be made through an envisioned social entrepreneurship. In the case of Tsambe Community, there are natural and human resources which can be developed for the purpose of social changes through socially-conscious marketing. The objective of this paper is to examine the sustainable behaviors through design thinking, where social entrepreneurship can impact on the lives of the people of Tsambe Community, thereby changing behavioral models such as rural-urban migration. It is also aimed at introducing suitable solutions to the social problems of the Tsambe people in their community through socially-conscious marketing, making the available resources known to private and public sectors, Non-Governmental Organizations as well as International Community. This paper is a conceptual study with content analysis as a method adopted for the purpose of data collection. The findings thus, shows that solutions to social problems facing the Tsambe community will therefore promote community development through purposeful innovations. Also, there will be reduction of rural-urban migration which in turn can cause urban congestion, armed robbery, prostitution and neglecting the potential that will lead to rural development.